Analisis Cedera Engkel pada Atlet Sepakbola - Khapi, Muhammad; Mashud; Arifin , Ramadhan (MAN Insan Cendekia Jambi, 2025)
This research aims to describe quantitatively and qualitatively the types, frequency, causes, and handling of sports injuries in PS Kab Tapin football athletes. The research method used is a survey with multiple-choice questionnaires and open-ended questions distributed to 20 athletes, as well as structured interviews with 10 athletes who have a history of ankle injuries. Quantitative data are analyzed descriptively, while qualitative data are analyzed through data reduction, data presentation, and conclusion drawing. The results show that all athletes (100%) have experienced injuries, with ankle injuries being the most common type (50%). The main factors causing injuries are collisions with other players (35%) and misstep when landing (30%). Injury management is most often carried out by the club's medical team (80%), and the dominant injury prevention is primary prevention (95%). In-depth interviews reveal that ankle injuries often occur due to match activities, with symptoms of pain, swelling, and bruising. The initial management applied by the majority of athletes is the RICE method (Rest, Ice, Compression, Elevation) and consultation with a physiotherapist. The conclusion of this study is that ankle injuries are a major issue faced by PS Kab Tapin football athletes, with a high incidence and the risk of recurrence. Prevention through warming up, muscle strengthening, and the use of protective equipment is highly recommended to reduce the incidence of injuries. Proper management and consistent rehabilitation are required to expedite recovery and prevent long-term complications.